1986
DOI: 10.1139/v86-113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation of serine β-lactones by Mitsunobu cyclization: synthesis and use of L-serine stereospecifically labelled with deuterium at C-3

Abstract: . VEDERAS. Can. J. Chem. 64, 706 (1986).The ring closure of N-benzyloxycarbonyl-L-serine (1) under Mitsunobu conditions (Ph3P, dimethyl azodicarboxylate, -78°C) to give the corresponding p;lactone (2) is shown by deuterium and oxygen-18 labelling studies to proceed by hydroxy group activation, in contrast to analogous cyclizations of more hindered P-hydroxy acids, which usually occur by carboxy group activation. Samples of 1 stereospecifically labelled with deuterium at C-3 were prepared by hydrogenation of (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Conceptually,¯-lactones can be prepared by activation of either the hydroxyl or carboxyl groups of monoesters Scheme 7. Reagents and conditions: (a) D1AD, TPP, THF, room temperature, 3 h. [16][17][18][19][20][21][22]. Among the different methods of lactonization of¯-hydroxyacids described in the literature, we chosen the Mitsunobu reaction [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually,¯-lactones can be prepared by activation of either the hydroxyl or carboxyl groups of monoesters Scheme 7. Reagents and conditions: (a) D1AD, TPP, THF, room temperature, 3 h. [16][17][18][19][20][21][22]. Among the different methods of lactonization of¯-hydroxyacids described in the literature, we chosen the Mitsunobu reaction [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…The experiment was done with the monoester (9) (3 g, 13.7 mmol), PPh 3 (3.61 g) in THF (60 ml) and DIAD (2.72 ml) in THF (6 ml). After the puri cation, the lactone (16) (17). The experiment was realized with the monoester (10) (2.66 g, 12.2 mmol), PPh 3 (3.20 g) in THF (30 ml) and DIAD (2.40 ml) in THF (4 ml).…”
Section: General Procedurementioning
confidence: 99%
“…Following a scheme developed by Arnold et al (Arnold et al 1985Ramer et al 1986 ;Williams, 1989), the synthesis of SAIL cystine ((2R,2kR,3S,3S)- [1,1k,2,2k,3,3k-13 C 6 ,2,2k-15 N 2 ; 3,3k-2 H 2 ]cystine) could be accomplished with a 35% overall yield, although potentially risky chemicals, such as dimethyl azodicarboxylate, were used. To avoid potentially hazardous reaction materials, a more easily accessible means to synthesize the stereoisomer at the b-position of SAIL cysteine was also examined (Fig.…”
Section: Cysteinementioning
confidence: 99%
“…19,20 "Soft" nucleophiles such as thiolate tend to attack the b-carbon whereas "hard" nucleophiles such as alkoxide or hydroxide target the carbonyl. 21 Nitrogen nucleophiles may attack at either site. 22 In previous studies, serine or threonine residues in proteins were shown to attack b-lactones at the carbonyl to give acylated products.…”
Section: Reaction Of N-cbz-l-serine B-lactone With Hav 3c Protease C24smentioning
confidence: 99%